Poetry of the Bima Kingdom as a Counter-Narrative to Colonialism, Scientism, Anthropocentrism and Radicalism - Umar, Umar; Mardan, Mardan; Aksa, Aksa (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This article discusses Syair Kingdom Bima, a 19th-century Malay poem from the Bima Sultanate, as a counter-narrative that challenges dominant discourses of colonialism, scientism, anthropocentrism, and radicalism. Through a new historicism and intertextuality approach, this article examines the narrative strategy of the Bima Kingdom Syair in guiding power dynamics. By focusing on the internal conflict and ethical complexity within the Bima Sultanate, the poem implicitly rejects colonial narratives. This emphasizes the importance of local knowledge systems and the importance of ethical leadership rooted in Islamic principles. Bima Kingdom Poetry's depiction of the relationship between humans, nature and God is in sharp contrast to the Western scientific and anthropocentric view which prioritizes human power over nature. The poem interprets the eruption of Mount Tambora as being caused by a cosmic imbalance caused by human actions (the Sultan of Tambora's violation of the moral and spiritual order). By advocating spiritual transformation and moral introspection, Syair Kingdom Bima offers a solution to radicalism.